Electrophysiologic and behavioral responses mediated by volatiles involved in the repellency of Apis mellifera (Lepeletier) (Hymenoptera: Apidae) - Pires, Patricia Daniela da Silva; Sant’Ana, Josué; Bisotto-de-Oliveira, Ricardo (EntomoBrasilis, 2020)
Repellent volatiles to insects might be an important tool for management of bees in areas which the presence of these organisms is not required. This study aimed to evaluate the electroantennal and behavioral responses of Africanized honeybees (workers), Apis mellifera (Lepeletier) (Hymenoptera Apidae), at different ages, to benzaldehyde (BA) and methyl anthranilate (MA) and to evaluate the potential repellency of these compounds under field conditions. Laboratory tests were conducted to study electroantennographic responses (mV) and chemotactic behavior of worker bees aged 1-5 (young) and 20-30 (old) days in four choice olfactometer. Electrophysiological responses to each compound did not differ between young and old workers. Bees antennae (young) triggered significantly greater responses to BA, in the older ones, a higher response was observed to MA, both compared to control (ethanol). The threshold response to BA and MA was achieved at 10 µg/µL, both compounds repelled bees at the same dose in olfactometer. Treatments with BA and MA, in field conditions, were less visited by scouter honey bees than those without these compounds (control).